Rethinking Remuneration Laws for the Financial Sector - Jonathan Ben Shlomo; Tristan Nguyen (Credit and Capital Markets – Kredit und Kapital, 2013)
Excessive risk-taking in the banking industry has led to the default of firms and to increased systemic risks as demonstrated during the previous financial crisis. The causes of this excessive risk taking are numerous and complex. However, it is now consensus that inappropriate remuneration structures can contribute to excessive risk taking. Substantial parts of the financial sector CEOs' variable compensations has a short-term focus and are not risk adjusted as empirical surveys have shown. Such remuneration structures persist in the aftermath of the crisis as part of the finance industry's remuneration culture. This, however, is inefficient from a risk perspective and thus triggers the need for a remuneration regulation. With the entrenchment of the Directives for the European Union in December 2010 and the implementation into national laws, e.g. Germany, UK and France, the remuneration focus substantially shifted to a more long-term perspective. Our analysis shows the reform efforts to aim in the right direction. However, the methodology for and the measurement of "success" should be revised. Due to different regulations in different European countries there is danger of regulatory arbitrage. Additionally, the new remuneration laws are given in the form of general principles leaving room for interpretation. Efficient regulation should ensure remuneration policies and structures to be aligned with an effective risk management. The financial authorities should therefore closely observe the market development in this perspective and take countermeasures if necessary. Furthermore, an elimination of existing regulatory flaws in national laws is needed. (K33, G30, G38, J33) – – Überdenken der Vergütungsvorschriften für den Finanzsektor Übertriebene Risikobereitschaft der Banken hat zu Zahlungsausfällen von Unternehmen und gestiegenen systemischen Risiken geführt, wie z.B. während der Finanz- und Wirtschaftskrise geschehen. Ursachen für diese übermäßige Risikobereitschaft sind vielschichtig und komplex. Jedoch besteht Konsens darin, dass unpassende Vergütungsstrukturen zu erhöhter Risikobereitschaft beitragen. Empirische Studien haben gezeigt, dass wesentliche Teile der variablen Vergütung von Spitzenmanagern auf kurzfristige Orientierung ausgerichtet sind und keine Risikoanpassung aufweisen. Solche Vergütungsstrukturen gehören auch in Zeiten nach der Finanzkrise immer noch zum Teil der Vergütungskultur vieler Unternehmen. Diese sind jedoch aus der Risikoperspektive heraus ineffizient und bedürfen einer grundlegenden Regulierung der Vergütungsstrukturen. Mit der Verankerung der Richtlinien für Europäische Union im Dezember 2010 und der Implementierung in nationales Recht z.B. in Deutschland, im Vereinigten Königreich und Frankreich wurde der Vergütungsfokus hin zu einer langfristigeren Perspektive verschoben. Unsere Analyse zeigt, dass die Reformbemühungen zwar in die richtige Richtung zielen, die Methodik und Messung des Erfolgs jedoch noch überarbeitet werden sollte. Aufgrund der verschiedenen Vorschriften in verschiedenen europäischen Ländern besteht die Gefahr von Regulierungsarbitrage. Außerdem bieten die neuen Vergütungsgesetze, die oft sehr allgemein formuliert sind, Raum für Interpretationen. Effiziente Regulierung sollte sicherstellen, dass Vergütungspraktiken- und Strukturen auf ein wirksames Risikomanagement ausgerichtet werden. Die Finanzbehörden sollten deshalb die Marktentwicklung in dieser Hinsicht genau beobachten und wenn erforderlich Gegenmaßnahmen einleiten. Schließlich ist es notwendig Regulierungslücken in den nationalen Gesetzen zu beseitigen. (K33, G30, G38, J33)
Keywords: 330